Annie and the Boys. - Grier, David Alan (Computer (00189162), 2007)
In this article the author discusses the origin and history of spreadsheet computer programs. He describes the first time he saw one in the late 20th century, the early era of personal computing. Discussed is the competition among software firms to develop their own version of spreadsheet software. The author notes the increase in development of computers that could run IBM-compatible software. The author analyzes a copyright lawsuit over software development brought by one firm against another and the disputed judgement that resulted.